Injectable-free regimens containing bedaquiline, delamanid, or both for adolescents with rifampicin-resistant tuberculosis in Khayelitsha, South Africa. (March 2020) - Mohr-Holland, Erika; Reuter, Anja; Furin, Jennifer; Garcia-Prats, Anthony; De Azevedo, Virginia; Mudaly, Vanessa; Kock, Yulene; Trivino-Duran, Laura; Isaakidis, Petros; Hughes, Jennifer
Abstract: Background: Limited data exist on the use of bedaquiline and delamanid in adolescents with rifampicin-resistant tuberculosis (RR-TB). We describe RR-TB treatment of adolescents (10–19 years) with injectable-free regimens containing these drugs in Khayelitsha, South Africa. Methods: This retrospective study included adolescents initiating injectable-free RR-TB treatment regimens containing bedaquiline and/or delamanid from February 2015 to June 2018. We report adverse events (AEs) of interest, sputum culture conversion (SCC), and final end-of-treatment outcomes. Findings: Twenty-two patients were included; median age at treatment initiation was 17 years (interquartile range [IQR] 15-18), and six (27%) were HIV-positive (median CD4 count 191 cells/mm3 [IQR 157-204]). Eight (36%) patients had RR-TB with fluoroquinolone resistance; ten (45%), eight (36%), and four (18%) patients received regimens containing bedaquiline, delamanid, or the combination of bedaquiline and delamanid, respectively. The median durations of exposure to bedaquiline and delamanid were 5·6 (IQR 5·5-8·4) and 9·4 (IQR 5·9-14·4) months, respectively. There were 49 AEs of interest which occurred in 17 (77%) patients. Fourteen (64%) patients had pulmonary TB with positive sputum cultures at bedaquiline and/or delamanid initiation; among these SCC at month 6 was 79%. Final end-of-treatment outcomes for the 22 adolescent were: 17 (77%) successfully treated, two (9%) lost-to-follow-up, two (9%) treatment failed, and one (5%) died. Interpretation: This study found that injectable-free regimens containing bedaquiline and/or delamanid in a programmatic setting were effective and well tolerated in adolescents and should be routinely provided for RR-TB treatment in this age group as recommended by the World Health Organisation.